Peran Agama dalam Pembentukan Karakter Manusia pada Lembaga Pendidikan - Fauzan, Fauzan; Dannur, Moh (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
Islam is a perfect religion that governs all of aspects of human life. Religion should be the key of all human life problems , because following to the concept of religion will be the solution to all of the problems. The role of religion is very dominant in humans, because humans have actually been bound by a contract when God began to create humans in the form of a fetus, where humans have acknowledged and testified to God . This paper is expected to provide a demand to anyone who reads in order to understand how they can live in the world by following the concepts and instructions of religion so that they become characterized to thier God, human being, and to thier environment. By having the character as guided by religion, it will make people able to freely life in the world, and in the hereafter will be glorified by God.